2010
DOI: 10.1590/s1806-66902010000400010
|View full text |Cite
|
Sign up to set email alerts
|

Radiation balance in a soybean ecosystem in the Amazon

Abstract: The continuous advance of the agricultural border in the Amazon has been worrying the scientific community due to the possible environmental impacts caused by this change in land use. The present work evaluated the behavior of the radiation balance components over the soybean crop (Glycine Max (L.) Merryl) in an Amazon area of continuous advance of the agricultural border. The radiation components were continuously monitored during the soybean cycle in 2006 and 2007 in an area of 200 ha. The soybean cultivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
2
4
0
2
Order By: Relevance
“…The natural ecosystems (PF and SF) presented higher Rn, ET, and EF and lower albedo, G, and H than did the anthropic ecosystems (PA and AG). A small are comparable to those obtained here (Culf et al, 1995;Shuttleworth, 1989;Souza, Rocha, Ribeiro, & Souza, 2010 Our results for G showed that AG had, on average, the highest values (96 W m −2 ), followed by PA (92 W m −2 ), SF (57 W m −2 ), and was a drought year; therefore, the land surface was subjected to drier conditions than in 2004. The mechanisms of interaction between solar radiation and canopy physiology, which are dependent by both the plant (i.e., stomatal conductance and the root networks, which exploit soil water) and environmental conditions (i.e., T air and vapour pressure deficit), are most likely to have a greater impact than water availability in ET over forests in this part of Amazonia (Albert et al, 2018;Christoffersen et al, 2014;de Oliveira et al, 2017;Rocha et al, 2004).…”
Section: Surface Energy and Water Fluxes For Different Land-cover Tsupporting
confidence: 89%
See 1 more Smart Citation
“…The natural ecosystems (PF and SF) presented higher Rn, ET, and EF and lower albedo, G, and H than did the anthropic ecosystems (PA and AG). A small are comparable to those obtained here (Culf et al, 1995;Shuttleworth, 1989;Souza, Rocha, Ribeiro, & Souza, 2010 Our results for G showed that AG had, on average, the highest values (96 W m −2 ), followed by PA (92 W m −2 ), SF (57 W m −2 ), and was a drought year; therefore, the land surface was subjected to drier conditions than in 2004. The mechanisms of interaction between solar radiation and canopy physiology, which are dependent by both the plant (i.e., stomatal conductance and the root networks, which exploit soil water) and environmental conditions (i.e., T air and vapour pressure deficit), are most likely to have a greater impact than water availability in ET over forests in this part of Amazonia (Albert et al, 2018;Christoffersen et al, 2014;de Oliveira et al, 2017;Rocha et al, 2004).…”
Section: Surface Energy and Water Fluxes For Different Land-cover Tsupporting
confidence: 89%
“…Now, a more comprehensive analysis can be conducted concerning the dynamics of albedo, Rn, G, H, ET, and EF over different ecosystems in the study area. A small are comparable to those obtained here (Culf et al, 1995;Shuttleworth, 1989;Souza, Rocha, Ribeiro, & Souza, 2010 was a drought year; therefore, the land surface was subjected to drier conditions than in 2004. The natural ecosystems (PF and SF) presented higher Rn, ET, and EF and lower albedo, G, and H than did the anthropic ecosystems (PA and AG).…”
Section: Surface Energy and Water Fluxes For Different Land-cover Tsupporting
confidence: 86%
“…The field experiment for soybeans (maize), with a continuous extension of 200 (23) ha, was conducted in Paragominas (02˚59S, 47˚21W, Figure 1) located in the northeastern part of Para state in the east part of the Amazon basin [31]. In Paragominas, large landholders are changing their economic activities from ranching to production of soybeans which may increase the pressure on the Amazon basin forest.…”
Section: Crop Modeling Approachmentioning
confidence: 99%
“…A grande maioria dos estudos teóricos e experimentais de balanço de radiação em comunidades vegetais concentra-se principalmente em dosséis com distribuição homogênea das plantas no plano horizontal (André et al, 2010;Sauer et al, 2007;Souza et al, 2010). Nas últimas décadas, com vistas à melhor compreensão do consumo de água e da fotossíntese na escala da planta, tem-se investido no estudo da interação da energia radiante em copas de espécies arbóreas que formam dosséis descontínuos (Angelocci et al, 2004;Green et al, 2001;Landsberg et al, 1975;McNaughton et al, 1992;Thorpe, 1978).…”
Section: Introductionunclassified